The half-life of maternal transplacental antibodies against diphtheria, tetanus, and pertussis in infants: an individual participant data meta-analysis - Oguti, B; Ali, A; Andrews, N; Barug, D; Anh Dang, D; Halperin, SA; Thu Hoang, HT; Holder, B; Kampmann, B; Kazi, AM; Langley, JM; Leuridan, E; et al. (Elsevier, 2021)
Aim There are few reliable estimates of the half-lives of maternal antibodies to the antigens found in the primary series vaccines. We aimed to calculate the half-lives of passively acquired diphtheria, tetanus and pertussis (DTP) antibodies in infants. We aimed to determine whether decay rates varied according to country, maternal age, gestational age, birthweight, World Bank income classifications, or vaccine received by the mother during pregnancy. Methods De-identified data from infants born to women taking part in 10 studies, in 9 countries (UK, Belgium, Thailand, Vietnam, Canada, Pakistan, USA, Guatemala and the Netherlands) were combined in an individual participant data meta-analysis. Blood samples were taken at two timepoints before any DTP-containing vaccines were received by the infant: at birth and at 2-months of age. Decay rates for each antigen were log2-transformed and a mixed effects model was applied. Half-lives were calculated by taking the reciprocal of the absolute value of the mean decay rates. Results Data from 1426 mother-infant pairs were included in the analysis. The half-lives of the 6 antigen-specific maternal antibodies of interest were similar, with point estimates ranging from 28.7 (95% CI: 24.4 – 35) days for tetanus toxoid antibodies to 35.1 (95% CI: 30.7 – 41.1) days for pertactin antibodies. The decay of maternal antibodies did not significantly differ by maternal age, gestational age, birthweight, maternal vaccination status or type of vaccine administered. Conclusion Maternal antibodies decay at different rates for the different antigens; however, the magnitude of the difference is small. Decay rates are not modified by key demographic or vaccine characteristics.